OPTIMASI ALGORITMA C4.5 MENGGUNAKAN PARTICLE SWARM OPTIMIZATION (PSO) UNTUK KLASIFIKASI PENYEBAB PERCERAIAN - Nafillah (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan)
The number of divorces that occur in Indonesia is increasing every year, from the data that is known that most divorce cases are carried out by couples under the age of 35 years, the cause also varies from domestic violence, economic factors, infidelity, incompatibility, etc. From the existing divorce data, it is necessary to extract information to predict what factors are causing the divorce. In this study will use the C4.5 algorithm as a classification and prediction method, which will be optimized using the PSO (Particle Swarm Optimization) algorithm to improve the performance of the C4.5 algorithm. From the data mining process, the classification is produced with an accuracy of 87.4%, the accuracy level is higher when compared to the previous research which is only 57.63%. Keywords: Divorce rate, divorce factor, C4.5 Algorithm, PSO Algorithm, Optimization.